CPD article: Guiding the owner: the use of supplements in canine osteoarthritis management. (2nd December 2021) - Lowe, Robyn
Abstract : Owners often reach for over-the-counter supplements for the management of canine osteoarthritis, believing them to be natural, side effect-free options. Some may ask for your opinion as a veterinary professional, whereas others will come to you already using certain products. It is imperative to be aware of the evidence for the relevant products and to encourage the use of good quality products as the first option. The aim should be to help prevent owners of arthritic dogs wasting their money buying multiple products with little or no evidence to back up their use, to be wary of bold unsubstantiated claims for improvements or health benefits, and to ensure that supplements are not used as a sole intervention for the management of arthritic pain, as they are unlikely to have the evidence base to support this claim.